المقارنة بين فعالية أوندانسيترون وميتوكلوبراميد في العلاج الدوائي للإقياءات الحملية - الدالي, عصام; حسن, سحر; علي, نوار (Latakia University Journal -Medical Sciences Series, 2018)
* The study was made on a sample of 100 pregnancies with Hyperemesis Gravidarum whom admitted to Tishreen University Hospital, Lattakia,Department of Obstetrics and Gynecology,during the period of April 2016 until May 2017 . * The efficacy of ondansetron and metoclopramide was studied in the treatment of hyperemesis gravidarum and the most important side effects during treatment was studied . * We found a significant reduction in the frequency of vomiting and severity of nausea on the third day of treatment in both closely studied groups (pvalue = 0.9489) and( pvalue = 0.826) respectively . * The fetal pulse was normal throughout the treatment days in both groups. * Ondansetron and metoclopramide showed similar efficacy in the treatment of hyperemesis gravidarum, as well as in nausea relief, while side effects were more frequent when metoclopramide was used. * Ondansetron can be recommended as a first line in the treatment of hyperemesis gravidarum in the hospital (Intravenous) because of its good efficacy and low side effects. أجريت الدراسة على عينة مكونة من 100 حالة من المريضات الحوامل المقبولات بقصة إقياءات حملية في قسم التوليد وأمراض النساء في مستشفى تشرين الجامعي – اللاذقية خلال الفترة الممتدة من نيسان 2016 حتى أيار 2017. تم دراسة فعالية كل من أوندانسيترون وميتوكلوبراميد في علاج الإقياءات الحملية ودراسة أهم التأثيرات الجانبية خلال المعالجة . وجدنا انخفاض واضح في تواتر الإقياءات وشدة الغثيان في اليوم الثالث من العلاج في كلا المجموعتين المدروستين بشكل متقارب p value =0.9489 ) ) و p value = 0.826)) على التوالي . نبض الجنين كان طبيعيا خلال طيلة أيام العلاج في كلا المجموعتين المدروستين . أظهر كلا من أوندانسيترون وميتوكلوبراميد فعالية متشابهة في علاج الإقياءات الحملية , وكذلك في تخفيف الغثيان , بينما كانت الآثار الجانبية أكثر حدوثا عند استعمال ميتوكلوبراميد . يمكن التوصية باستخدام أوندانسيترون كخط أول في علاج الإقياءات الحملية وريديا" داخل المشفى بسبب فعاليته الجيدة وقلة آثاره الجانبية .